1998
DOI: 10.1144/gsl.sp.1998.131.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Southern hemisphere palaeobathymetry

Abstract: Digital grids, with a spatial resolution of 0.5 °, were compiled using batbymetry, sediment thickness and oceanic crustal ages for the southern hemisphere to calculate sedimentfree palaeobathymetric charts for late Cretaceous (110 Ma) to the present. These reconstructions allow the definition and quantification of the bathymetric evolution of the seaways and gateways within this region. Pre-60 Ma the palaeobathymetry and the interconnection of the deeper ocean basin was dominated by the formation of hotspot-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Our modeled age of the oceanic lithosphere correlates well with the dated samples from the drill sites (Figure b). We do not see a perfect one‐to‐one correlation, which may partly be influenced by inaccuracies in dating, as some of the drill site ages are based on the oldest sediment age (Sykes et al, ). However, this is not significant as seen from Figure b, the scatter of data may rather suggest that random uncertainty dominates.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Our modeled age of the oceanic lithosphere correlates well with the dated samples from the drill sites (Figure b). We do not see a perfect one‐to‐one correlation, which may partly be influenced by inaccuracies in dating, as some of the drill site ages are based on the oldest sediment age (Sykes et al, ). However, this is not significant as seen from Figure b, the scatter of data may rather suggest that random uncertainty dominates.…”
Section: Discussionmentioning
confidence: 74%
“…(section 3.4). The location of drill sites used bySykes et al (1998) and for comparison with our results are shown in yellow on the map. For reference, we show all other DSDP/ODP/IODP sites in the Indian Ocean (red circles).…”
mentioning
confidence: 99%
“…More recently, Sykes et al . 5 calculated sediment-free paleobathymetric reconstructions at 0.5 degrees resolution for the southern hemisphere using present-day bathymetry, sediment thickness and seafloor age grids. They were able to show acceptable correlations (∼500–700 m) with paleobathymetric estimates from a handful (6 in the South Atlantic) of DSDP and ODP drill sites.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the ACC and Antarctic Bottom Water (AABW) are strongly guided by seafloor topography [e.g., Lazarus and Caulet, 1993;Rack, 1993]. Recent palaeobathymetric models were based on the kinematics and thermal subsidence rates of oceanic crust [e.g., Sykes et al, 1998;Brown et al, 2006], but lack any consideration of the effects of sediment distribution. For greater accuracy, sediment accumulations should also be taken into account in the next generation of paleobathymetric reconstructions.…”
Section: Introductionmentioning
confidence: 99%